No hay paso: barriers to nature access faced by Mexicans in southern Arizona - Crocker, Rebecca M.; Sánchez, Josselyne Diomara; Cruz, Gabriel Alvin (Frontiers in Public Health, 2025)
IntroductionMexican immigrants and other low-income populations in the United States face reduced access to natural environments, limiting their opportunities both to secure a wide range of associated health advantages and to participate fully in environmental stewardship and protection efforts. This ethnographic study was designed to investigate Mexicans’ access to and engagement with natural environments over the course of international migration from Mexico to southern Arizona to help fill important gaps in our understanding of the intersectional nature barriers faced in this population.MethodsWe conducted interviews with stakeholders and historical experts (n = 9) and first- generation Mexican immigrants working in land-based careers (n = 10) to explore nature barriers in a current and historical context. Analysis was conducted utilizing a One Health adaptation of the National Institute of Minority Health and Health Disparities research framework.ResultsOur analysis revealed barriers across all six levels of influence (planetary, interspecies, society, community, interpersonal, and individual) and multiple domains, including aridification of land, international migration, disruption to interspecies’ relationships, discrimination, lack of time and energy, and emotional distress tied to immigration status.DiscussionThis article confirms multilevel barriers identified in the literature as well as highlights additional barriers not previously recorded. This suggests the need for further research and especially health interventions geared to increase immigrants’ access to nature to improve their health and heighten their ability to serve as effective advocates and stewards of the natural world.